The teacher/pupil ratio from the practice of stage required in middle school - Guimaraes, Luiz Ernesto [UNESP]; Lanza, Fabio (Univ Estadual Sudoeste Bahia, 2015)
This article examines some of the issues related to the teacher/pupil ratio, having in view some challenges exist in public school today. Realizing education composed of various actors, this work prioritizes the figure of the teacher and the student in the learning process in the school environment. The study counted with the field research carried out in the school of public education of Parana, in the city of Londrina, in 2009. Developed during the probationary period required, the present work is the result of the practice of observation and intervention, in the discipline of Sociology.
Keywords: Education; Teach of sociology; Stage required